Clinical Sports Medicine - Alt A; Malcherek N; Geisler S; Thietje R (Deutsche Zeitschrift für Sportmedizin, 2020)
Non-specific low back pain (NLBP) affected every fourth Swiss citizen in 2018. The aims of this prospective randomized controlled trial were to determine which therapeutic strategy is most effective and sustainable to reduce NLBP and avoid chronification of non-chronic NLBPinpatients in Switzerland. The therapy effects were compared between a combination of progressive exercise and two counseling units (ECG, N=22 / 59% women) and a combination of two counseling and nine units each with mobilization of the lumbar spine, the sacroiliac joint, and a massage of the back muscles (MCG, N=22 / 41 % women). Intensity of disability and pain were measured (NRS = Numeric Rating Scale, ODI = Oswestry Disability Index) after the first, fifth, ninth treatment and after weeks six and 16.The first three measurements did not show anyeffects, but the last two measurements showed significant positive therapy effects (p < 0.05) for both measuring instruments (NRS, ODI) for the ECG. This study should help to better understand the physiotherapeutic possibilities of sustainable therapy in patients with non-chronic NLBP under realistic conditions adapted to the Swiss healthcare system. The ECG showed sustainable therapy effectiveness and beneficial approaches to avoid chronification. Further long-term research seems to be particularly important in this respect.KEY WORDS: Cognitive Behavioural Factors, Progressive Exercises, Counseling, Manual Therapy, Treatment Costs